A review on synthetic chalcone derivatives as tubulin polymerisation inhibitors - Wenjing Liu; Min He; Yongjun Li; Zhiyun Peng; Guangcheng Wang (Taylor & Francis Group, 2022)
Microtubules play an important role in the process of cell mitosis and can form a spindle in the mitotic prophase of the cell, which can pull chromosomes to the ends of the cell and then divide into two daughter cells to complete the process of mitosis. Tubulin inhibitors suppress cell proliferation by inhibiting microtubule dynamics and disrupting microtubule homeostasis. Thereby inducing a cell cycle arrest at the G2/M phase and interfering with the mitotic process. It has been found that a variety of chalcone derivatives can bind to microtubule proteins and disrupt the dynamic balance of microtubules, inhibit the proliferation of tumour cells, and exert anti-tumour effects. Consequently, a great number of studies have been conducted on chalcone derivatives targeting microtubule proteins. In this review, synthetic or natural chalcone microtubule inhibitors in recent years are described, along with their structure-activity relationship (SAR) for anticancer activity.